Pembentukan Religiusitas Remaja Muslim: Tinjauan Deskriptif Analitis - Warsiyah, Warsiyah (Cendekia: Jurnal Kependidikan Dan Kemasyarakatan, 2018)
The study of the factors that shape the religiosity of Muslim youth is important given the many cases of deviant behavior reported both through mass media and research results involving Muslim youth. This is because religiosity has an important role in human self-control because it can affect attitudes, perceptions, emotions and even on their behavior. This paper is an analytical study of various related literature sources on factors that can shape the religiosity of Muslim youth. The discussion begins with a study of the definition and dimensions of Muslim religiosity, the development of the religious psyche in humans, the factors that shape adolescent religiosity. The results of the discussion show that the dominant factors of shaping the religiosity of Muslim adolescents are the religious behavior of parents, Islamic religious education in school, and peer conformity.ØªØ¹ØªØ¨Ø± Ø¯Ø±Ø§Ø³Ø© Ø§ÙØ¹ÙØ§ÙÙ Ø¹Ù ØªØ¯ÙÙÙ Ø§ÙØ´Ø¨Ø§Ø¨ Ø§ÙÙØ³ÙÙ ÙÙÙØ© Ø¨Ø§ÙÙØ¸Ø± Ø¥ÙÙ ÙØ«Ø±Ø© Ø§ÙØ³ÙÙÙ Ø§ÙÙÙØØ±Ù Ø§ÙØ°Ù ÙØ¸ÙØ± ÙÙ Ø®ÙØ§Ù ÙØ³Ø§Ø¦Ù Ø§ÙØ¥Ø¹ÙØ§Ù ÙÙØªØ§Ø¦Ø¬ Ø§ÙØ£Ø¨ØØ§Ø« Ø§ÙØªÙ ÙØ´Ø§Ø±Ù ÙÙÙØ§ Ø§ÙØ´Ø¨Ø§Ø¨ Ø§ÙÙØ³ÙÙ. ÙØ°Ø§ ÙØ£Ù Ø§ÙØªØ¯ÙÙ ÙÙ Ø¯ÙØ± ÙÙÙ ÙÙ Ø¶Ø¨Ø· Ø§ÙÙÙØ³ Ø§ÙØ¨Ø´Ø±Ù ÙØ£ÙÙ ÙÙÙÙ Ø£Ù ÙØ¤Ø«Ø± Ø¹ÙÙÙÙ ÙÙ Ø§ÙÙÙØ§ÙÙ ÙØ§ÙØªØµÙØ±Ø§Øª ÙØ§ÙØ¹ÙØ§Ø·Ù ÙØ§ÙØ³ÙÙÙÙØ§Øª. ÙØ°Ù Ø§ÙÙØ±ÙØ© ÙÙ Ø¯Ø±Ø§Ø³Ø© ØªØÙÙÙÙØ© ÙÙÙØµØ§Ø¯Ø± ÙØ§ÙÙØ±Ø§Ø¬Ø¹ Ø§ÙÙØ®ØªÙÙØ© Ø°Ø§Øª Ø§ÙØµÙØ© ÙÙØ¹ÙØ§ÙÙ Ø§ÙØªÙ ÙÙÙÙ Ø£Ù ØªÙÙÙÙÙ ØªØ¯ÙÙÙ Ø§ÙØ´Ø¨Ø§Ø¨ Ø§ÙÙØ³ÙÙ. ØªØ¨Ø¯Ø£ Ø§ÙÙÙØ§ÙØ´Ø© Ø¨Ø¯Ø±Ø§Ø³Ø© Ø¹Ù ØªØ¹Ø±ÙÙ ÙØ£Ø¨Ø¹Ø§Ø¯ ØªØ¯ÙÙ Ø§ÙÙØ³ÙÙØ ÙØªØ·ÙØ± Ø§ÙÙÙØ³ Ø§ÙØ¯ÙÙÙØ© ÙØ¯Ù Ø§ÙØ¨Ø´Ø ÙØ§ÙØ¹ÙØ§ÙÙ Ø§ÙØªÙ ØªÙÙÙÙÙ ØªØ¯ÙÙ Ø§ÙÙØ±Ø§ÙÙÙÙ. ÙØªØ¸ÙØ± ÙØªØ§Ø¦Ø¬ Ø§ÙÙÙØ§ÙØ´Ø© Ø£Ù Ø§ÙØ¹ÙØ§ÙÙ Ø§ÙÙØ¤Ø«Ø±Ø© ÙÙ ØªÙÙÙÙ ØªØ¯ÙÙ Ø´Ø¨Ø§Ø¨ Ø§ÙÙØ³ÙÙÙÙ ÙÙ Ø§ÙØ³ÙÙÙ Ø§ÙØ¯ÙÙÙ ÙÙØ¢Ø¨Ø§Ø¡Ø ÙØ§ÙØªØ±Ø¨ÙØ© Ø§ÙØ¯ÙÙÙØ© Ø§ÙØ¥Ø³ÙØ§ÙÙØ© ÙÙ Ø§ÙÙØ¯Ø±Ø³Ø©Ø ÙÙØ·Ø§Ø¨ÙØ© Ø§ÙØ²ÙÙØ§Ø¡.